2022
DOI: 10.1021/acs.analchem.1c04873
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Two-Dimensional Liquid Chromatography-Mass Spectrometry Platform for Simultaneous Multi-Attribute Characterization of Adeno-Associated Viruses

Abstract: Adeno-associated viruses (AAVs) are non-enveloped, single-stranded DNA viruses that have recently emerged as an attractive vector for delivering genetic materials to hosts for gene therapy applications. Due to their ability to transduce a wide range of species and tissues in vivo, low risk of immunotoxicity, and mild innate and adaptive immune responses, AAVs are currently used in research and clinical studies as a monotherapy or with other biomolecules to perform gene editing, replacement, addition, and silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…However, TFA as a mobile phase additive is generally not recommended for use with MS due to its ion-suppressing effects , and necessitated desolvation gas modification to improve MS signal intensity. Alternatively, both Zhang et al and Wu et al found success in AAV VP separation utilizing DFA as a mobile phase additive for RP chromatography, although without achieving separation of AAV2 VP1 and VP2 proteins. , Given that DFA has a similar effect on analyte separation as TFA without negatively impacting MS signal intensity during MS analysis, pairing it with HILIC has the potential to provide separation of AAV2 VP2 and VP1 proteins without impacting the quality of the MS spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TFA as a mobile phase additive is generally not recommended for use with MS due to its ion-suppressing effects , and necessitated desolvation gas modification to improve MS signal intensity. Alternatively, both Zhang et al and Wu et al found success in AAV VP separation utilizing DFA as a mobile phase additive for RP chromatography, although without achieving separation of AAV2 VP1 and VP2 proteins. , Given that DFA has a similar effect on analyte separation as TFA without negatively impacting MS signal intensity during MS analysis, pairing it with HILIC has the potential to provide separation of AAV2 VP2 and VP1 proteins without impacting the quality of the MS spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid chromatography–mass spectrometry (LC–MS) is increasingly utilized for the characterization of AAV VPs with hydrophilic interaction liquid chromatography (HILIC) and reversed-phase (RP) chromatography being the two LC separation phases most used. ,, Complete separation of VP1, VP2, and VP3 is desired for comprehensive intact VP characterization and effective determination of VP ratios, with multiple recent intact VP separation studies illustrating an ability to achieve complete VP separation of multiple serotypes. ,, However, separation of VP2 and VP1 of AAV2 has been shown to be difficult to achieve and those that succeed in full VP separation of AAV2 suffer from MS ion suppression effects . Additionally, VP separation is only part of what is required if it is desired to apply such strategies within a quality control (QC) environment, something increasingly necessitated by the increased use of AAV vectors in cell and gene therapies.…”
Section: Introductionmentioning
confidence: 99%
“…77 More recently, an online 2DLC-MS platform that coupled AEX as the first dimension and RPLC as the second dimension was developed to analyse adeno-associated viruses (AAVs) with online Review doi.org/10.1002/ansa.202300016 desalting. 78 The Tholey group utilised SCX to reduce the abundance of low-charged ions prior to RPLC separation using monolithic columns and MS detection to characterise low molecular weight (MW) proteomes and short open reading frame-encoded peptides (SEPs) using combined bottom-up proteomics (BUP) and TDP. 79 A variant of IEX, chromatofocusing, utilises a pH gradient to focus proteins based on their pI values.…”
Section: Ion Exchange Chromatography -Based Multidimensional Separationsmentioning
confidence: 99%
“…In this study, offline fractions from WAX were dialysed to remove the salt before being subjected to RPLC–MS analysis 77 . More recently, an online 2DLC–MS platform that coupled AEX as the first dimension and RPLC as the second dimension was developed to analyse adeno‐associated viruses (AAVs) with online desalting 78 . The Tholey group utilised SCX to reduce the abundance of low‐charged ions prior to RPLC separation using monolithic columns and MS detection to characterise low molecular weight (MW) proteomes and short open reading frame‐encoded peptides (SEPs) using combined bottom‐up proteomics (BUP) and TDP 79 …”
Section: Introductionmentioning
confidence: 99%
“…21 While intact measurements are important to understand the number of VP subunits and cargo, denatured analysis is also of great significance for evaluating the modification in the subunits. For example, Liu et al denatured and ruptured an intact AAV capsid and then chromatographically separate individual VP subunits for detection with fluorescence and MS. 6,32 This subunit analysis method provided unique selectivity for VPs of a variety of AAV serotypes. Additionally, VPs with post-translational modifications (PTMs), including oxidation and phosphorylation, were also distinguished using this approach.…”
Section: ■ Introductionmentioning
confidence: 99%